Modulation of host cell metabolism by T4SS-encoding intracellular pathogens - Hayek, Inaya; Berens, Christian; Lührmann, Anja (Current Opinion in Microbiology, 2019)
Intracellular bacterial pathogens intimately interact with the infected host cell to prevent elimination and to ensure survival. One group of intracellular pathogens, including Coxiella burnetii, Legionella pneumophila, Brucella spp., Anaplasma phagocytophilum, and Ehrlichia chaffeensis, utilizes a type IV secretion system (T4SS) that injects effectors to modulate host cell signalling, vesicular trafficking, autophagy, cell death and transcription to ensure survival [1]. So far, little emphasis has been directed towards understanding how these bacteria manipulate host cell metabolism. This manipulation is not only important for gaining access to nutrients, but also for regulating specific virulence programs [2,3]. Here, we will summarize recent progress made in characterizing the manipulation of host cell metabolism by C. burnetii and other intracellular pathogens utilizing a T4SS.
CRIS-Team Scopus Importer:2019-06-25